Characterization of the Methanomicrobial Archaeal RNase Zs for Processing the CCA-Containing tRNA Precursors - Wang, Xiaoyan; Gu, Xien; Li, Jie; Yue, Lei; Li, Defeng; Dong, Xiuzhu (Frontiers in Microbiology, 2020)
RNase Z is a widely distributed and usually essential endoribonuclease involved in the 3-end maturation of transfer RNAs (tRNAs). A CCA triplet that is needed for tRNA aminoacylation in protein translation is added by a nucleotidyl-transferase after the 3-end processing by RNase Z. However, a considerable proportion of the archaeal pre-tRNAs genetically encode a CCA motif, while the enzymatic characteristics of the archaeal RNase (aRNase) Zs on CCA-containing pre-tRNAs remain unclear. This study intensively characterized two methanomicrobial aRNase Zs, the Methanolobus psychrophilus mpy-RNase Z and the Methanococcus maripaludis mmp-RNase Z, particularly focusing on the properties of processing the CCA-containing pre-tRNAs, and in parallel comparison with a bacterial bsu-RNase Z from Bacillus subtilis. Kinetic analysis found that Co2+ supplementation enhanced the cleavage efficiency of mpy-RNase Z, mmp-RNase Z and bsu-RNase Z for 1400-, 2990- and 34-fold respectively, and Co2+ is even more indispensable to the aRNase Zs than to bsu-RNase Z. Mg2+ also elevated the initial cleavage velocity (V0) of bsu-RNase Z for 60.5-fold. The two aRNase Zs exhibited indiscriminate efficiencies in processing CCA-containing vs. CCA-less pre-tRNAs. However, V0 of bsu-RNase Z was markedly reduced for 1520-fold by the CCA motif present in pre-tRNAs under Mg2+ supplementation, but only 5.8-fold reduced under Co2+ supplementation, suggesting Co2+ could ameliorate the CCA motif inhibition on bsu-RNase Z. By 3-RACE, we determined that the aRNase Zs cleaved just downstream the discriminator nucleotide and the CCA triplet in CCA-less and CCA-containing pre-tRNAs, thus exposing the 3-end for linking CCA and the genetically encoded CCA triplet, respectively. The aRNase Zs, but not bsu-RNase Z, were also able to process the intron-embedded archaeal pre-tRNAs, and even process pre-tRNAs that lack the D, T, or anticodon arm, but strictly required the acceptor stem. In summary, the two methanomicrobial aRNase Zs use cobalt as a metal ligand and process a broad spectrum of pre-tRNAs, and the characteristics would extend our understandings on aRNase Zs.